Triple dose of gadolinium-DTPA and delayed MRI in patients with benign multiple sclerosis. Issue 5 (May 1996) - Filippi, M; Capra, R; Campi, A; Colombo, B; Prandini, F; Marcianò, N; Gasparotti, R; Comi, G
Abstract : OBJECTIVES–To evaluate whether a triple dose of gadolinium-DTPA (Gd-DTPA) or delayed MRI increase the number, size, and conspicuousness of enhancing lesions in patients with benign multiple sclerosis. METHODS–T1 weighted brain MRI was carried out on 20 patients with benign multiple sclerosis (expanded disability status scale < 3 with a disease duration > 10 years) in two sessions. In the first session, one scan was obtained before and two scans five to seven minutes and 20-30 minutes after the injection of 0.1 mmol/kg Gd-DTPA (standard dose). In the second session, six to 24 hours later, the same procedure was repeated with 0.3 mmol/kg Gd-DTPA (triple dose). RESULTS–Nine enhancing lesions were found in seven patients (35%) using the standard dose of Gd-DTPA. The numbers of enhancing lesions increased to 13 (P = 0.03) and the number of patients with such lesions to eight (40%) on the delayed standard dose scans. On the early triple dose scans, we found 19 enhancing lesions in 10 patients (50%). The number of enhancing lesions was significantly higher (P = 0.01) than that obtained with the early standard dose. The number of enhancing lesions was 18 and the number of "active" patients 11 (55%) on the delayed triple dose scans. The enhancing areas increased progressively from the early standard dose scans to the delayed triple dose scans. The contrast ratios of the lesions detected in early standard dose scans was lower than those of lesions present in the early (P = 0.01) and delayed (P = 0.04) triple dose scans. CONCLUSIONS–More enhancing lesions were detected in patients with benign multiple sclerosis with both delay of MRI and the use of triple dose of Gd-DTPA suggesting that the amount of inflammation in the lesions of such patients is mild and heterogeneous.